Soldiers as victims: behind military barracks in the post-colonial African army. Issue 1 (2nd January 2017) - Maringira, Godfrey
ABSTRACT: This paper examines the ways in which the military infringes on the social and political rights of soldiers who joined the Zimbabwe National Army in post-independence Zimbabwe. Contrary to the scholarly and policy debates that present Zimbabwean soldiers as the silent prop behind President Robert Mugabe and the perpetrators of political violence, this paper argues that these soldiers have also been victimised in army barracks. The victimhood of soldiers has been explicit in the ways in which they are forced to execute their duties beyond their professional expectations. In substantiating this argument, the paper explores the unethical military training and the ways in which soldiers are disciplined and punished through Chapter 11:02 of the draconian Defence Act. The paper's contribution stems from a 'rights' perspective that emphasises the right to freedom, justice and protection, which is usually quite silent in the military. But the question is how can soldiers' concerns be translated into new practices without compromising so-called 'state security'?